2014
DOI: 10.4103/1008-682x.122592
|View full text |Cite
|
Sign up to set email alerts
|

Testis-specific Fank1 gene in knockdown mice produces oligospermia via apoptosis

Abstract: Fank1 is exclusively expressed in the testis from the meiosis phase to the haploid phase of spermatogenesis. In this study, we examined the function of Fank1 by establishing a Fank1-knockdown transgenic mouse model. The apoptotic statuses of the testes of the transgenic mice were tested using the terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) method. The FANK1 consensus DNA-binding sequence was identified using cyclic amplification of sequence target (CAST) analysis. Differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…It is well established that programmed cell death (PCD) plays a principal role in processes of mammalian spermatogenesis [ 32 ]. Apoptosis, a type of PCD, plays a primary role during the different stages of spermatogenesis and has been widely studied [ 16 , 33 , 34 ]. However, the role of autophagy, another type of PCD which is equally important in spermatogenesis [ 35 ], still remains to be explored [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that programmed cell death (PCD) plays a principal role in processes of mammalian spermatogenesis [ 32 ]. Apoptosis, a type of PCD, plays a primary role during the different stages of spermatogenesis and has been widely studied [ 16 , 33 , 34 ]. However, the role of autophagy, another type of PCD which is equally important in spermatogenesis [ 35 ], still remains to be explored [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is of note that previous studies have shown a significant correlation between testis specific transcripts, like phospholipase zeta, protamine 1, CAPZA3, and Fank1 with sperm concentration ( 30 , 31 ). Therefore, it is likely that low expression of testis transcript is associated with efficiency of spermatogenesis.…”
Section: Discussionmentioning
confidence: 73%
“…It was reported that Dusp1, Klk1b21 and Klk1b27 were overexpressed in Fank1 -knockdown mice and may be direct targets of Fank1 (Dong et al, 2014). However, in Fank1 −/− testis, a reduction of Klk1b21 and Klk1b27 mRNA was detected but no increase in Dusp1 transcripts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The fibronectin type 3 and ankyrin repeat domains 1 gene ( Fank1 ) is an ancient, evolutionarily conserved gene present in vertebrates and expressed from the meiosis phase to the haploid phase of spermatogenesis in the testis (Zheng, Zheng & Yan, 2007). As a DNA binding protein, FANK1 recognizes the DNA sequence AAAAAG, and is implicated as a transcription factor during spermatogenesis (Dong et al, 2014). In a study of short-hairpin RNA (shRNA)-based knockdown transgenic mouse model, a reduction in sperm number and an increase in apoptotic germ cells were observed (Dong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation